Knowledge, attitude and application of computer by Bachelor Level Nursing students - Shami, M (Journal of Institute of Medicine Nepal, 2013)
Background: Computer literacy and information literacy are critical to the future of nursing in this 21st century. The objective of the study is to identify the knowledge, attitude and application of computer by the BN 1st year nursing students. Methods: The study populations were 108 Bachelor of Nursing 1st year nursing students of the three different institutions. The research has adapted descriptive cross-sectional design. In this research study, purposive non- probability convenient sampling technique was adopted to select the nursing institutes. A self-administered structured questionnaire, Likert scale and semi structured questionnaire were used. Results: The majority of the respondents (44.4%) were from Central development region. The majority of the respondents (59.3%) had taken basic course on computer training. Also, Majority of the respondents 33.3% respondents had average knowledge on E-mail and Internet. Interestingly, majority (54.9%) respondents had used computer for medical information occasionally. Similarly, majority of the respondents (69.7%) strongly disagreed that ‘without computer, world would be better.’ Majority of the respondent (37%) often used Internet/E-mail and chatting in computer. Likewise, the majority of the respondents (40.7%) stated that computer is very useful in nursing education and research. Conclusion: The findings of the study indicate that there was a deficit in students. IT competencies should be integrated into the BN 1st year course. DOI: http://dx.doi.org/10.3126/joim.v34i2.9046 Journal of Institute of Medicine August, 2012; 34:2 21-27